Effect of vital dyes on human corneal endothelium and elasticity of Descemet’s membrane - Weber, Isabell P.; Rana, Mrinal; Thomas, Peter B. M.; Dimov, Ivan B.; Franze, Kristian; Rajan, Madhavan S. (PLoS ONE, 2017)
The purpose of this study was to evaluate the effects of vital dyes on human Descemet’s membranes (DMs) and endothelia. DMs of 25 human cadaveric corneas with research consent were treated with dyes routinely used in Descemet membrane endothelial keratoplasty (DMEK), 0.05% Trypan blue (TB) or a combination of 0.15% Trypan blue, 0.025% Brilliant blue and 4% Polyethylene glycol (commercial name Membrane Blue Dual; MB). The effects of these two dyes on (i) endothelial cell viability, (ii) DM mechanical properties as assessed by atomic force microscopy, and iii) qualitative DM dye retention were tested for two varying exposure times (one or four minutes). No significant differences in cell toxicity were observed between treatments with TB and MB at the two different exposure times (P = 0.21). Further, both dyes led to a significant increase in DM stiffness: exposure to TB and MB for one minute increased the apparent elastic modulus of the DM by 11.2% (P = 8*10−3) and 17.7%, respectively (P = 4*10−6). A four-minute exposure led to an increase of 8.6% for TB (P = 0.004) and 13.6% for MB (P = 0.03). Finally, at 25 minutes, the dye retention of the DM was considerably better for MB compared to TB. Taken together, a one-minute exposure to MB was found to improve DM visibility compared to TB, with a significant increase in DM stiffness and without detrimental effects on endothelial cell viability. The use of MB could therefore improve (i) visibility of the DM scroll, and (ii) intraoperative unfolding, enhancing the probability of successful DMEK surgery.
CRIS-Team Scopus Importer:2020-08-12